Nephrococcus serbicus, a new coccoid cyanobacterial species from Božana Cave, Serbia - Popović, Slađana; Simić, Gordana Subakov; Korać, Aleksandra; Golić, Igor; Komárek, Jiří (Phytotaxa, 2016)
During the investigation of cyanobacterial diversity in Božana Cave, which is situated in a limestone region in western Serbia, a new species of cyanobacterium belonging to the genus Nephrococcus was found. So far, there are only three records of the genus Nephrococcus in the whole world (recorded in China and Nepal), which was reviewed and is presented in this study. Detailed morphology of the examined cyanobacterium was documented by digital photography and drawings using light and confocal laser microscopy. Ecology (temperature, relative humidity and light intensity) and biofilm parameters (chlorophyll-a, the water content and the content of organic/inorganic matter in the biofilm) were also measured, and the associated taxa described. Detailed morphological characteristics that indicated the differences between this species from those already known, allowed us to describe this cyanobacterium as a new species, Nephrococcus serbicus. This is the first record of the genus Nephrococcus in the territory of Europe.